Analysis of the first positive polarity gigantic jet recorded near the Yellow Sea in mainland China. (1st September 2019) - He, Qijia; Yang, Jing; Lu, Gaopeng; Chen, Zhixiong; Wang, Yu; Sato, Mitsuteru; Qie, Xiushu
Abstract: At 12:16:22 UTC on 12 August 2010, a gigantic jet (GJ) was recorded over a thunderstorm near the Yellow Sea in China. The extremely low-frequency (ELF) magnetic field recorded at the Onagawa Observatory indicates that this GJ transferred positive charge from the thundercloud to the ionosphere (namely a +GJ event), which is the first observation of a +GJ reported in mainland China. The top altitude of this GJ was estimated to be about 89 km. The parent thunderstorm formed in a very moist environment (precipitable water of 75.4 mm) with moderate convective available potential energy (1294 J/kg) and lifted index (−3.19), and strong 0–6 km wind speed shear (16.3 m/s). The meteorological parameters are not much different from typical summer thunderstorms. The area of cloud top brightness temperature colder than −60 °C (altitudes above 14 km) increased significantly after 10:00 UTC and reached the maximum at 12:00 UTC (16 min before the GJ), suggesting the occurrence of the GJ was related to the strong vertical development of the thunderstorm. Around the time of the GJ, the south cell of the storm featured overshooting top as indicated by radar data. Additionally, the storm was dominated by negative cloud-to-ground (-CG) flashes with an increase in -CG flash rate around the time of the GJ occurrence, indicating the storm appeared to be of normal polarity (the main positive charge region located above the main negative charge region). The + GJ was probably produced by a normally electrified thunderstorm, and a possible explanation for this unexpected behavior and different lightning activity of GJ-producing storms were discussed. Highlights: This is the first observation of a positive gigantic jet (+GJ) in mainland China, with clearly ELF magnetic field signals. Aims to enrich the research of +GJs and investigate characteristics of environmental conditions that produced GJs. Detailed analysis of the parent thunderstorm and lightning activity of this +GJ. Discussed the different lightning activities of GJ-producing thunderstorms and the production mechanism of this +GJ.